2019
DOI: 10.1097/md.0000000000014802
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant occurrence of primary renal non-Hodgkin lymphoma and a colon cancer

Abstract: Rationale:Primary renal lymphoma (PRL) is a rare malignancy due to the absence of lymphatic tissues in the kidney, and patients with PRL have been reported to have a poor prognosis due to its rapid invasiveness and limited treatment strategies. Colon cancer is the third most common cancer, and has a high mortality rate. Both malignant diseases predominantly affected elderly men; however, a case with concomitant occurrence of the 2 cancers is extremely rare.Patient concerns:A 78-year-old male patient with abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…61 Some of the patients with PRNHL showed underlying diseases such as HIV, 26,72 HCV, 33 Sjogren, 53 prostatic adenocarcinoma, 9 Bell's palsy, 6 limbic encephalitis, 73 lung cancer, 3,17 urothelial carcinoma, 17 gastric cancer, 8 and colon cancer. 75 One patient had renal cell carcinoma in the same kidney as a separate nodule. 34 Imaging modalities have been reported to be helpful for the diagnosis of PRNHL before histopathologic diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…61 Some of the patients with PRNHL showed underlying diseases such as HIV, 26,72 HCV, 33 Sjogren, 53 prostatic adenocarcinoma, 9 Bell's palsy, 6 limbic encephalitis, 73 lung cancer, 3,17 urothelial carcinoma, 17 gastric cancer, 8 and colon cancer. 75 One patient had renal cell carcinoma in the same kidney as a separate nodule. 34 Imaging modalities have been reported to be helpful for the diagnosis of PRNHL before histopathologic diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Though the 2 malignancies shared similarities in gender and age, without findings of common genetic features, concomitant occurrence is an exceptional event and rarely reported. Ji Li, MM et al 18 reported a case of concomitant PRL and colon cancer in 78 years old male patient. This patient having a family history of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In (10), C D (P i ) represents the result of Gaussian filter. Weight coefficient is optimized by the mean gradient values of two-pixel neighborhoods.…”
Section: Improvement Of the Nonlocal Mean (Nlm) Algorithmmentioning
confidence: 99%
“…ese methods can play a significant role in localization and characterization of lesions, but only the lesions in lumen can be observed. Gastrointestinal wall infiltration, the relationship between tumors, and adjacent tissues cannot be shown clearly [10][11][12]. Magnetic resonance imaging (MRI) can examine pelvic cavity from different angles and display colon cancer ideally.…”
Section: Introductionmentioning
confidence: 99%